Stability of frozen fillets from silver catfish anesthetized with essential oil of Lippia alba prior to electrical stunning or hypothermia. Issue 5 (2nd January 2017) - Veit, Juliana C.; Piccolo, Jaqueline; Scherer, Aline F.; Machado, Isadora S.; Peres, Marcelle M.; Schwerz, Janaina P.; Baldisserotto, Bernardo; Heinzmann, Berta M.; Emanuelli, Tatiana
Abstract: The effects of anesthesia with essential oil (EO) of L. alba prior to electrical stunning or hypothermia were evaluated on the stability of silver catfish fillets during frozen storage. Electrically stunned fish had the greatest increase in lipid oxidation along the storage and previous anesthesia with EO potentialized this effect. Fish stunned by hypothermia with no previous anesthesia had higher lipid oxidation in the flesh immediately after slaughtering, which probably contributed to accelerate protein oxidation along the storage. Fish stunned by hypothermia had the highest springiness value by the end of storage and the highest changes in instrumental color along the storage, whereas electrically stunned fish had delayed protein oxidation and smaller color and texture changes during frozen storage. Thus, hypothermia induced greatest changes in physico‐chemical markers and previous anesthesia with the EO of L. alba did not prevent these changes and did potentialize lipid oxidation induced by electrical stunning. Practical applications: There is a growing interest for natural anesthetics in commercial aquaculture and essential oils have been lately used with this purpose for fish husbandry and management. The use of natural anesthetics in pre‐slaughter steps, however, has been scarcely investigated. Stressful procedures during pre‐slaughter and slaughter steps can adversely affect fish flesh properties and the association of anesthetics with other stunning or killing methods could be an alternative to reduce fish stress and assure flesh quality. Our study, however, revealed that fillet stability during frozen storage is not improved by fish anesthesia with essential oil prior to hypothermia or electrical stunning. In addition, we also revealed that electrical stunning yielded greater fillet stability during frozen storage compared with hypothermia. These results are relevant in the search of humane fish stunning methods that provide the greatest flesh quality and stability.